Correlation of variable method to touristic demand prevision: an application to aiming at planning touristic development in south Brazilian region - Feger, Jose Elmar (2011)
Planning is an essential tool to delineate an action in any organization. To analyze and to decision-making in a productive arrangement, when it’s considered as a system, one of the important variables is its demand. The thematic of the study presented here concerns about a demand prevision making when statistic data base isn’t available. The alternative presented is a correlation variables method, which uses comparative statistic method, utilizing one touristic system that knows data with reference. The aim was to apply the methodology in a real case, analyzing its utility for a touristic planning and to create one attractive index that can be incorporated to econometric formula, for more precision on future analysis. Two questions oriented the study: how bigger can a touristic region “A” be? What is its attractive index? The methodology followed a descriptive approach, with transversal cut, delineated as case study. As result it was identified possible demand increasing at 3,8%, with 0,95 attractive index. It’s a preliminary and limited indicator; however, it becomes important if used in initial steps of planning process.